The developing world's bulging (but vulnerable) "middle class" - Ravallion, Martin (2012)
The "developing world's middle class" is defined here as those who are not poor when judged by the median poverty line of developing countries, but are still poor by US standards. The "Western middle class" is defined as those who are not poor by US standards. Although barely 80 million people in the developing world entered the Western middle class over 1990-2002, economic growth and distributional shifts allowed an extra 1.2 billion people to join the developing world's middle class. Four-fifths came from Asia, and half from China. Most of the new entrants remained fairly close to poverty, with incomes now bunched up just above $2 a day. The vulnerability of this new middle class to aggregate economic contractions is evident in the fact that one in six people in the developing world live between $2 and $3 per day. Over time, the developing world has become more sharply divided between countries with a large middle class and those with a relatively small one, with Africa prominent in the latter group. Poor people in countries with smaller middle classes may well be more exposed to slowing economic growth.